Recent development of flat supercontinuum generation in specialty optical fibers - Liu Huanhuan (Institue of Optics and Electronics, Chinese Academy of Sciences, 2019)
Supercontinuum (SC) generation has attracted a significant scientific interest in the past decades due to its promising applications covering the fields of metrology, spectroscopy, defense, as well as medical treatments. To date, researchers are devoted to improving the spectral width and flatness of SC generation by using specialty optical fibers. The flatness of the spectrum is of importance because it can improve the accuracy of measurement in practical applications. This paper summarizes the theory of SC, the state of the art of flat SC generation using optical fiber including photonic crystal fibers, soft glass fibers as well as germania-doped fibers, and suggests the future research direction of flat SC light source.